The Role of Pharmacological Treatment in the Chemoreflex Modulation - Langner-Hetmańczuk, Anna; Tubek, Stanisław; Niewiński, Piotr; Ponikowski, Piotr (Frontiers in Physiology, 2022)
From a physiological point of view, peripheral chemoreceptors (PCh) are the main sensors of hypoxia in mammals and are responsible for adaptation to hypoxic conditions. Their stimulation causes hyperventilation—to increase oxygen uptake and increases sympathetic output in order to counteract hypoxia-induced vasodilatation and redistribute the oxygenated blood to critical organs. While this reaction promotes survival in acute settings it may be devastating when long-lasting. The permanent overfunctionality of PCh is one of the etiologic factors and is responsible for the progression of sympathetically-mediated diseases. Thus, the deactivation of PCh has been proposed as a treatment method for these disorders. We review here physiological background and current knowledge regarding the influence of widely prescribed medications on PCh acute and tonic activities.